2015
DOI: 10.1002/pip.2729
|View full text |Cite
|
Sign up to set email alerts
|

High efficiency UMG silicon solar cells: impact of compensation on cell parameters

Abstract: High efficiency solar cells have been fabricated with wafers from an n-type Czochralski grown (Cz) ingot using 100% Upgraded Metallurgical-Grade (UMG) silicon feedstock. The UMG cells fabricated with a passivated emitter and rear totally diffused (PERT) structure have an independently confirmed cell efficiency of 19.8%. This is the highest efficiency reported for a cell based on 100% UMG silicon at the time of publication. The current and power losses are analysed as a function of measured material parameters,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 46 publications
0
6
0
1
Order By: Relevance
“…6 This was then followed by a 19% n-type UMG Cz homojunction cell one year later. 7 Recently, Rougieux et al 12 reported a 19.8% efficient Passivated Emitter Rear Totally diffused (PERT) cell using 100% UMG n-type Cz.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…6 This was then followed by a 19% n-type UMG Cz homojunction cell one year later. 7 Recently, Rougieux et al 12 reported a 19.8% efficient Passivated Emitter Rear Totally diffused (PERT) cell using 100% UMG n-type Cz.…”
mentioning
confidence: 99%
“…However, a heavy phosphorus diffusion will significantly increase recombination on the non-metallised portion of the rear side, for a device with a full rear-side diffusion, such as the Passivated Emitter and Rear Totally diffused (PERT) cells we have reported previously on similar material. 12 Therefore, a PERL structure was selected to minimise the area of the diffused regions to achieve high efficiency UMG solar cells. Crucially, the localization of the diffusion at the rear side is achieved by an-etch back process, instead of being diffused locally into the contact area, in order to maintain a full-area gettering effect.…”
mentioning
confidence: 99%
“…However, the high cost of PV cells made from conventional solar grade silicon is a hindrance to the rapid growth of the PV industry. One promising alternative is to use PV cells made from upgraded metallurgical grade silicon (UMG-Si) purified via the metallurgical process route [2][3][4]. The production of UMG-Si can be five times more energy efficiency than the conventional Siemens process to produce solar grade silicon; hence, the cost of UMG-Si is much lower [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Мультикристаллический кремний (мультикремний), полученный методом направленной кристаллизации из высокочистого рафинированного металлургического кремния, так называемый UMG кремний, с одной стороны, является доступным и недорогим материалом для фотоэлектропреобразователей (ФЭП). Из монокристалла, выращенного из UMG кремния, к настоящему времени произведены солнечные элементы с эффективностью 19.8% [1]. С другой стороны, повышенное содержание примесей в нем оказывает неблагоприятное влияние на электрофизические свойства мультикремния.…”
Section: Introductionunclassified